Biologické výzkumy ostrova Jamese Rosse. - Biodiverzita sinic a řas - Elster, J. (Josef); Komárek, J. (Jiří); Nedbalová, L. (Linda) (2013)
Description of microphyte communities, particularly of cyanobacteria and algae in the terrestrial and freshwater habitats of the northern deglaciated part of the James Ross Island, NW Weddell Sea, coastal Antarctica.